GLOBAL REGULATORY ASPECTS OF WOUND CARE AND BURN DRESSINGS - VibhuYadav; ParikshitBansal; AmitMittal; Singh, Sachin Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to present an overview of regulatory requirements for wound and burn care dressings. Methods: A total of 80 research and review articles including regulatory guidelines to control the marketing of wound and burn care dressings recommended by international regulatory agencies were reviewed. Results: A wide range of dressings, as a new target of the healing process, have been developed due to continued growth and innovations in the field. Ideal dressings should be safe and achieve healing at a reasonable cost with minimum inconvenience to patients. It is mandatory that manufacture and sale of such dressings are approved by the relevant health authority of each country. This article provides manufacturers with an overview regarding regulatory approval procedures for marketing such dressings in different countries and addresses the gaps and challenges in the existing guidelines aimed at maintaining product quality. It provides a comparative analysis of the differences in regulatory requirements and highlights that ongoing discussions and appropriate actions are required to support the continuous development of these dressings. Most countries have their own regulatory guidelines, and the approval processes differ according to the country. Quality parameters concerning the type of material, pore size, sterilization methods, shape and size, and labeling are not discussed in guidelines; therefore, innovators and manufacturers are facing tough challenges to showcase their products in the market, and this further leads to either lack of market availability or high cost of such dressings. Conclusion: Development of common quality guidelines is essential for market availability of low-cost, high-quality dressings.